Evaluation of platelet indexes as potential biomarkers of suspected pulmonary embolism - Wójcik, Mariusz; Daszyk-Wójcik, Joanna; Skoczyński, Kamil (European Journal of Clinical and Experimental Medicine, 2019)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Pulmonary embolism is one of the most frequent cardiovascular diseases, potentially leading to death. There is no validated biomarker with both high specificity and sensitivity. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The aim of the study was to define the diagnostic importance of platelet count (PLT), mean platelet volume (MPV) and platelet distribution width (PDW) on acute pulmonary embolism. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. We retrospectively reviewed the medical records of 145 patients with clinically suspected acute pulmonary embolism admitted to the Emergency Department. Demographic data and laboratory tests were collected on admission. All patients underwent computed tomography (CT) angiography. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The total data of 145 patients were analyzed, including 65 patients (67±17 years; 30 men/35 women) with acute pulmonary embolism confirmed with CT and 80 patients (67±19 years; 26 men/54 women) with negative CT. The MPV did not differ between the patients with acute PE and the control group (8.0 fL [IQR: 7.6-8.4] vs. 7.9 fL [IQR: 7.4-8.7], p=0.45). There were no significant differences in PLT (220x10³/mm³ [IQR: 172-274] vs. 243x10³/mm³ [IQR: 186-286], p=0.12) and PDW (59.0 ± 6.9% vs. 57.2 ± 7.3%, p=0.12). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions. Our results suggest that platelet indexes (at a single time point) are not a reliable diagnostic biomarkers of acute pulmonary embolism.